B cells: roles in physiology and pathology of pregnancy - Liu, Jin-Chuan; Zeng, Qunxiong; Duan, Yong-Gang; Yeung, William S. B.; Li, Raymond H. W.; Ng, Ernest H. Y.; Cheung, Ka-Wang; Zhang, Qingqing; Chiu, Philip C. N. (Frontiers in Immunology, 2024)
B cells constitute a diverse and adaptable immune cell population with functions that can vary according to the environment and circumstances. The involvement of B cells in pregnancy, as well as the associated molecular pathways, has yet to be investigated. This review consolidates current knowledge on B cell activities and regulation during pregnancy, with a particular focus on the roles of various B cell subsets and the effects of B cell-derived factors on pregnancy outcomes. Moreover, the review examines the significance of B cell-associated autoantibodies, cytokines, and signaling pathways in relation to pregnancy complications such as pregnancy loss, preeclampsia, and preterm birth.